A systematic mapping study on enterprise architecture mining. Issue 5 (28th May 2019) - Perez-Castillo, Ricardo; Ruiz-Gonzalez, Francisco; Genero, Marcela; Piattini, Mario
ABSTRACT: Enterprise architecture allows companies to deal with digital transformation through the proactive presentation and alignment of business and IT in a holistic manner. One important challenge is EA modelling since it is time-consuming (thus expensive), error-prone, and biased owing to experts' subjective opinions. This challenge might consequently be addressed through automatic EA modelling. We conducted a systematic mapping study to classify and evaluate the research concerning EA mining proposals developed specifically for TOGAF and Archimate. After analysing results, we concluded that the research field is not sufficiently mature and further research on EA mining is necessary.